Ferromagnetic material pinned by weak domain wall and application thereof

By adding transition elements, rare earth elements and doping elements into ferromagnetic materials to form weak domain wall pinning ferromagnetic materials with an amorphous structure, the problem of domain wall pinning in the prior art affects domain wall movement is solved, the effect of reducing magnetic field strength and current density is achieved, and the reliability and durability of memory devices are improved.

CN119522029AActive Publication Date: 2025-02-25PEKING UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411629747.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Domain wall pinning in existing track magnetic memory seriously affects domain wall movement, increasing the magnetic field strength and current density required to drive domain wall movement, and reducing the reliability and durability of memory devices.

Method used

By incorporating transition elements, rare earth elements and doping elements into the ferromagnetic material, a weak domain wall pinned ferromagnetic material with an amorphous structure is formed, which reduces the density and intensity of the magnetic domain wall pinning site, thereby reducing the magnetic field strength and current density required to drive the movement of the domain wall.

Benefits of technology

The magnetic domain wall pinning site density and strength are significantly reduced, the magnetic field strength and current density required to drive the domain wall movement are reduced, and the reliability and durability of the memory device are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522029A_ABST
    Figure CN119522029A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ferromagnetic materials, in particular to a weak domain wall pinned ferromagnetic material and application thereof. The invention provides a weak domain wall pinned ferromagnetic material which comprises the following components in percentage by atomic number: 0-100% of transition element, 0-100% of rare earth element and 0-100% of doping element, and the sum of the transition element, the rare earth element and the doping element is 100%. The atomic number percentage of the transition element in the weak domain wall pinned ferromagnetic material is greater than the atomic number percentage of the rare earth element and the doping element, and the atomic number percentage of the rare earth element and the doping element in the weak domain wall pinned ferromagnetic material is not 0; the doping element comprises boron and / or nitrogen. The magnetic domain wall pinning site density and strength of the weak domain wall pinned ferromagnetic material are greatly reduced, and meanwhile, the current density and the magnetic field intensity required for driving the magnetic domain wall to move can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ferrimagnetic materials, and in particular to a ferrimagnetic material with weak domain wall pinning and application thereof. Background Art

[0002] The development of traditional silicon-based semiconductor logic chips is gradually approaching its physical limits, and the continuation of Moore's Law faces severe challenges. Spin logic devices have intrinsic non-volatile storage characteristics, which can realize storage and computing integration, thereby breaking through the technical bottlenecks of the von Neumann architecture in terms of speed and power consumption, and have become a key area of ​​focus in the current academic and industrial circles. Among many new spin electronics devices, spin logic devices based on domain wall motion can realize rich logical operation functions and are one of the important technical paths for the development of spin logic chips. Traditional ferromagnetic materials have large stray fields, and the magnetic moment is sensitive to external magnetic fields, which leads to reduced integration and reliability of ferromagnetic-based spin electronics devices. At the same time, the spin dynamics process of ferromagnets is generally on the nanosecond scale, which limits the further improvement of the device response speed. In contrast, ferrimagnetic materials (FiMs) have a smaller net magnetization due to the presence of two antiparallel magnetic sublattices inside them. At the magnetic compensation temperature, the magnetic moments of the two sets of magnetic lattices cancel each other out, and the macroscopic net magnetic moment is zero, which greatly reduces the stray field; at the angular momentum compensation temperature, the angular momentum of the two sets of magnetic lattices cancel each other out, and the macroscopic net angular momentum is zero. At this time, ferrimagnets exhibit excellent spin dynamics properties, such as higher SOT efficiency, longer spin coherence length, and ultrafast magnetodynamic behavior, which can reduce the energy consumption and response speed of spin electronics devices. Experimentally, the angular momentum and magnetic compensation temperature of ferrimagnets can be controlled in a variety of ways, so they have unique advantages in the application of new spin devices based on domain wall motion.

[0003] In the application of racetrack magnetic memory, domain wall pinning will seriously affect the movement of domain walls, increase the magnetic field strength and current density required to drive domain wall movement, and reduce the reliability and durability of memory devices. Therefore, people have begun to pay attention to methods to reduce domain wall pinning. However, existing racetrack memories use ferrimagnetic or doped magnetic metals, which have a large density and strength of domain wall pinning sites. Summary of the invention

[0004] The purpose of the present invention is to provide a ferrimagnetic material with weak domain wall pinning and its application. The density and strength of the magnetic domain wall pinning sites of the ferrimagnetic material with weak domain wall pinning are greatly reduced, and the magnetic field strength and current density required to drive the domain wall movement can be significantly reduced.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a ferrimagnetic material with weak domain wall pinning, which comprises, in terms of atomic percentage, 0-100% of transition elements, 0-100% of rare earth elements and 0-100% of doping elements, wherein the sum of the transition elements, the rare earth elements and the doping elements is 100%, and the atomic percentage of the transition elements in the ferrimagnetic material with weak domain wall pinning is greater than the atomic percentage of the rare earth elements and the doping elements, and the atomic percentage of the rare earth elements and the doping elements in the ferrimagnetic material with weak domain wall pinning is not 0;

[0007] The doping elements include boron and / or nitrogen.

[0008] Preferably, the ferrimagnetic material is an amorphous structure.

[0009] Preferably, the transition element includes one or more of Fe, Co and Ni.

[0010] Preferably, the rare earth element includes one or more of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc and Y.

[0011] Preferably, the transition element is Co, the rare earth element is Gd, and the doping element is B.

[0012] Preferably, the atomic percentage of Co in the ferrimagnetic material with weak domain wall pinning is 10.0% to 80.0%, the atomic percentage of Gd in the ferrimagnetic material with weak domain wall pinning is 10.0% to 80.0%, and the atomic percentage of B in the ferrimagnetic material with weak domain wall pinning is 10.0% to 80.0%.

[0013] Preferably, the atomic ratio of Co to B is 9:1 to 3:1.

[0014] The present invention also provides the use of the ferrimagnetic material pinned by the weak domain wall described in the above technical solution in magnetic storage spin electronics devices, magnetic logic spin electronics devices, magnetic field sensors or new soft magnetic materials.

[0015] The present invention provides a ferrimagnetic material with weak domain wall pinning, which comprises, in terms of atomic percentage, 0-100% of transition elements, 0-100% of rare earth elements and 0-100% of doping elements, wherein the sum of the transition elements, the rare earth elements and the doping elements is 100%, and the atomic percentage of the transition elements in the ferrimagnetic material with weak domain wall pinning is greater than the atomic percentage of the rare earth elements and the doping elements, and the atomic percentage of the rare earth elements and the doping elements in the ferrimagnetic material with weak domain wall pinning is not 0; the doping elements comprise boron and / or nitrogen. Ferrimagnetic materials (Fi M) have a smaller net magnetization intensity due to the existence of two antiparallel magnetic sub-lattices inside them. At the angular momentum compensation temperature, the angular momentum of the two sets of magnetic lattices cancel each other out, and the macroscopic net angular momentum is zero. At this time, the ferrimagnet exhibits excellent spin dynamics. The addition of doping elements into ferrimagnetic materials reduces the number and strength of pinning sites. After the doping elements enter the alloy, they will change the distance between magnetic atoms, change the bond length and coordination number, thereby changing the intensity of the exchange interaction. At the same time, they can also refine the grains and improve the amorphization effect, reduce grain boundaries and pinning, and thus greatly reduce the magnetic field intensity and current density required to drive domain wall motion. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A high-resolution cross-sectional TEM image of the ferrimagnetic material with weak domain wall pinning described in Example 1 (30.2%);

[0017] Figure 2 The ferrimagnetic material with weak domain wall pinning described in Example 1 (30.2%), Co, and the Co described in Comparative Example 1 80 B 20 and the Co 76 G 24 XAFS diagram of

[0018] Figure 3 A relationship curve diagram of the domain wall movement speed, magnetic field and current density of the ferrimagnetic materials with weak domain wall pinning described in Example 3 (19.1%), Example 4 (21.6%), Example 5 (25.1%), Example 6 (28.2%), Example 7 (29.2%) and Example 1 (30.2%) in the racetrack device;

[0019] Figure 4 The relationship curve (a) of the domain wall movement speed and magnetic field strength of the ferrimagnetic material with weak domain wall pinning described in Example 1 (30.2%) in the racetrack device at different temperatures and the relationship curve (b) of the domain wall movement speed and current density;

[0020] Figure 5A comparison chart of the effective depinning field and pinning density of the ferrimagnetic material with weak domain wall pinning described in Example 1 (30.2%) and other materials (Co, CoB, CoFeB, FeTb, GdMnAs, Co, CoFeB and CoGdB) in the Hall bar device;

[0021] Figure 6 Characterization of the pinning site density (a) and pinning site strength (b) of the ferrimagnetic materials pinned by weak domain walls of Example 3 (19.1%), Example 4 (21.6%), Example 5 (28.2%), Example 6 (29.2%), and Example 1 (30.2%);

[0022] Figure 7 Different configurations of domain walls of ferrimagnetic materials pinned by weak domain walls as described in Example 1 (30.2%) and ) at ultra-low current density (150A / cm 2 ) schematic diagram of domain wall motion;

[0023] Figure 8 Different configurations of domain walls of ferrimagnetic materials pinned by weak domain walls as described in Example 1 (30.2%) and ) at low current density (1.8 kA / cm 2 ) schematic diagram of domain wall motion. DETAILED DESCRIPTION

[0024] The present invention provides a ferrimagnetic material with weak domain wall pinning, which comprises, in terms of atomic percentage, 0-100% of transition elements, 0-100% of rare earth elements and 0-100% of doping elements, wherein the sum of the transition elements, the rare earth elements and the doping elements is 100%, and the atomic percentage of the transition elements in the ferrimagnetic material with weak domain wall pinning is greater than the atomic percentage of the rare earth elements and the doping elements, and the atomic percentage of the rare earth elements and the doping elements in the ferrimagnetic material with weak domain wall pinning is not 0;

[0025] The doping elements include boron and / or nitrogen.

[0026] In terms of atomic percentage, the ferrimagnetic material for weak domain wall pinning of the present invention includes 0 to 100% of transition elements, preferably 50% to 60%, and more preferably 55.2% to 57.6%. In the present invention, the transition elements preferably include one or more of Fe, Co and Ni, and more preferably include Co. When the transition elements are two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.

[0027] According to the percentage of atomic number, the ferrimagnetic material for weak domain wall pinning of the present invention includes 0 to 100% of rare earth elements, preferably 20% to 40%, and more preferably 28% to 31%. In the present invention, the rare earth elements preferably include one or more of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc and Y, and more preferably include Gd. When the rare earth elements are two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.

[0028] The ferrimagnetic material for weak domain wall pinning of the present invention comprises 0 to 100% of doping elements, preferably 10 to 20%, and more preferably 13.8 to 14.4%, in terms of atomic percentage. In the present invention, the doping elements comprise boron and / or nitrogen, preferably boron. When the doping elements are boron and nitrogen, the present invention has no special restrictions on the ratio of boron and nitrogen, and they can be mixed in any ratio.

[0029] In the present invention, the transition element in the ferrimagnetic material with weak domain wall pinning is preferably Co, the rare earth element is preferably Gd, and the doping element is preferably B; the atomic percentage of Co in the ferrimagnetic material with weak domain wall pinning is preferably 10.0% to 80.0%, and more preferably 50% to 70%; the atomic percentage of Gd in the ferrimagnetic material with weak domain wall pinning is preferably 10.0% to 80.0%, and more preferably 15% to 35%; the atomic percentage of B in the ferrimagnetic material with weak domain wall pinning is preferably 10.0% to 80.0%, and more preferably 12% to 20%.

[0030] In the present invention, the preparation method of the weak domain wall pinned ferrimagnetic material is preferably physical vapor deposition, molecular beam epitaxy, chemical vapor deposition, laser pulse deposition or laser direct writing; the physical vapor deposition is preferably evaporation coating or magnetron sputtering coating; more preferably magnetron sputtering.

[0031] In the present invention, the magnetron sputtering method preferably uses Co8B 20 The target material and the Gd target material are co-sputtered; the back vacuum of the magnetron sputtering method is preferably 5×10 -8 Torr, the sputtering pressure is preferably 3mTorr, the sputtering temperature is preferably 300K, Co8B 20 The sputtering power of is preferably 75 W, and the sputtering rate is preferably 0.028 nm / s; the sputtering power of Gd is variable, and when the sputtering power of Gd is 10 W, the sputtering rate is 0.018 nm / s (the sputtering rate increases linearly with the increase of the sputtering power), and the sample rotation speed is preferably 20 r / s.

[0032] The present invention does not have any special limitation on the process of evaporation coating, molecular beam epitaxy, chemical vapor deposition, laser pulse deposition or laser direct writing, and the process may be carried out using a process well known to those skilled in the art.

[0033] The present invention also provides the use of the ferrimagnetic material with weak domain wall pinning described in the above technical solution in magnetic storage spin electronics devices, magnetic logic spin electronics devices, magnetic field sensors or new soft magnetic materials. The present invention does not have any special limitation on the method of the application, and the method well known to those skilled in the art can be used.

[0034] The ferrimagnetic material with weak domain wall pinning provided by the present invention and its application are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0035] Example 1

[0036] Adopt Co8B 20 Target material (Co8B 20 The molar ratio of Co and B in the magnetron sputtering method is 8:20) and the Gd target is co-sputtered; the back vacuum of the magnetron sputtering method is 5×10 -8 Torr, sputtering pressure is 3mTorr, sputtering temperature is 300K, Co8B 20 The sputtering power of Gd is 75W, and the sputtering rate is 0.028nm / s; the sputtering power of Gd is variable, and the sputtering rate is 0.018nm / s when the sputtering power of Gd is 10W (the sputtering rate increases linearly with the increase of sputtering power), and the sample rotation speed is 20r / s, and the chemical composition is Co 55.8 G 30.2 B 14.0 The ferrimagnetic material with weak domain wall pinning (denoted as Co 56 G 30 B 14 ).

[0037] Examples 2 to 11 and Comparative Examples 1 to 2

[0038] The preparation processes of Examples 2 to 11 and Comparative Example 1 refer to Example 1, and the preparation condition parameters different from Example 1 and the chemical composition of the prepared weak domain wall pinned ferrimagnetic material are shown in Table 1:

[0039] In the preparation of Comparative Example 2, Co target and Gd target were co-sputtered; the back vacuum of the magnetron sputtering method was 5×10 -8Torr, the sputtering pressure is 3mTorr, the sputtering temperature is 300K, the sputtering power of Co is 75W, the sputtering rate is 0.041nm / s; the sputtering power of Gd is 23W, the sputtering rate is 0.041nm / s; the sample rotation speed is 20r / s, and the chemical composition is Co 76 G 24 ferrimagnetic material.

[0040] Table 1 Preparation conditions and chemical compositions of Examples 2 to 12 and Comparative Examples 1 to 2

[0041]

[0042] The ferrimagnetic material with weak domain wall pinning described in Example 1 was subjected to TEM test. The test results are as follows: Figure 1 As shown, Figure 1 In the figure, a is a cross-sectional high-resolution transmission electron microscope image with the multilayer structure marked, b is a Pt element resolution map, marked in red, c is a Co element resolution map, marked in blue, and d is a Gd element resolution map, marked in blue.

[0043] The ferrimagnetic material with weak domain wall pinning described in Example 1, amorphous Co, and the Co described in Comparative Example 1 are 80 B 20 and the Co 76 G 24 Perform XAFS test, the test results are as follows Figure 2 As shown, Figure 2 In ad, it means Co 76 G 24 and Co 56 G 30 B 14 XAS of different regions in the film at the Co K edge (a, b) and the Gd L3 edge (c, d). e and f are XAS of different regions in the film at the Co K edge (a, b) and the Gd L3 edge (c, d). 56 G 30 B 14 、Co、Co 80 B 20 and Co 76 G 24 The radial distribution function |χ(R)| of the experimental XAFS spectrum measured at the CoK edge of the film. The red dashed line represents the radial distribution function of the Co 56 G 30 B 14 The radial distribution function obtained from the three-dimensional atomic structure of Co 76 G 24 The radial distribution function of the Co atom is obtained from the three-dimensional atomic structure. 80 B 20 、Co76 G 24 and Co 56 G 30 B 14 XAS comparison of amorphous films (b), and XAS of Gd atoms and Gd, Co 76 G 24 and Co 56 G 30 B 14 XAS comparison of amorphous films (d).

[0044] Depend on Figures 1-2 It can be seen that the uniformity of the distribution of transition group atoms and rare earth atoms in the Co-Gd-B amorphous material is improved, the degree of amorphization is increased, and the domain wall pinning is reduced, while more Co-Gd atomic pairs increase the antiferromagnetic coupling chain to achieve fast spin dynamics, thereby accelerating the DW motion in Co-Gd-B.

[0045] The ferrimagnetic materials described in Example 3 (19.1%), Example 4 (21.6%), Example 5 (25.1%), Example 6 (28.2%), Example 7 (29.2%) and Example 1 (30.2%) were applied to a racetrack device, and the relationship between the domain wall movement speed and the magnetic field and the relationship between the domain wall movement speed and the current density were measured in the racetrack device at 298K. The test method is: applying a long current pulse in the racetrack device through a Keithley 2400 source meter, or applying a long current pulse to a Helmholtz coil to generate a pulsed magnetic field, measuring the position of the magnetic domain wall before and after the pulse current is applied, and thereby calculating the movement speed of the magnetic domain wall. The test results are as follows: Figure 3 As shown, a is a graph showing the relationship between the magnetic field driven magnetic domain wall movement speed and the magnetic field strength under different Gd contents; b is a graph showing the relationship between the current driven magnetic domain wall movement speed and the current density under different Gd contents; Figure 3 It can be seen that in a magnetic field of 0.03Oe or 1.8kA / cm 2 At a current density of 2.5 Å, the domain wall can move at a speed of 10 μm / s, indicating that the material has ultra-low domain wall pinning.

[0046] The ferrimagnetic material described in Example 1 was applied to a racetrack device, and the relationship between the domain wall movement speed and the magnetic field and the relationship between the domain wall movement speed and the current density were measured in the racetrack device using the same method at different temperatures. The test results are shown in Figure 2. Figure 4 As shown, a is a graph showing the relationship between the magnetic field driven magnetic domain wall movement speed and the magnetic field strength at different temperatures; b is a graph showing the relationship between the current driven magnetic domain wall movement speed and the current density at different temperatures; Figure 4 It can be seen that as the temperature increases, the pinning strength of the domain wall decreases, and the magnetic field and current density required to drive the domain wall movement decrease.

[0047] The ferrimagnetic materials described in Example 3 (19.1%), Example 4 (21.6%), Example 6 (28.2%), Example 7 (29.2%) and Example 1 (30.2%) were applied to a Hall bar device, in which the effective depinning field and density in Co-Gd-B were characterized, wherein Figure 5 The effective depinning field and pinning density of the ferrimagnetic material with weak domain wall pinning in the Hall bar device described in Example 1 are characterized, wherein a is Co, CoB, CoFeB (Co and CoB, respectively using Co target and Co 68 B 32 The target material is sputtered and grown at room temperature. For details, please refer to Appl. Phys. Lett. 96, 022501 (2010); Co 60 Fe 20 B 20 , using Co 60 Fe 20 B 20 The target is sputtered grown at room temperature and annealed in situ at 300°C for 2h. For details, please refer to Appl.Phys.Lett.103,182401(2013)). Comparison of the pinning site density in the ferrimagnetic material described in Example 1 (30.2%), b is FeTb, GdMnAs, Co, CoFeB (the preparation of FeTb and GdMnAs refers to Phys.Rev.Lett.117,057201(2016); the preparation of Co refers to Phys.Rev.Lett.99,217208(2007); the preparation of CoFeB refers to Appl.Phys.Lett.103,182401(2013).), comparison of the effective depinning field size in CoGdB; Figure 5 It can be seen that the chemical composition is Co 56 G 30 B 14 The weak domain wall pinned ferrimagnetic material has an ultraweak effective depinning field and an ultralow pinning density. Figure 6 The pinning site density (a) and pinning site strength (b) of the ferrimagnetic materials of Example 3 (19.1%), Example 4 (21.6%), Example 7 (29.2%) and Example 1 (30.2%) are characterized by Figure 6 It can be seen that the density and strength of domain wall pinning sites decrease with the increase of Gd content.

[0048] Figure 7 Different configurations of domain walls of ferrimagnetic materials pinned by weak domain walls as described in Example 1 (30.2%) and ) Schematic diagram of domain wall motion under ultra-low current density (the duration of applied current is 30 seconds, the starting position of the domain wall is indicated by a green line, and the scale bar is 50 μm). 2 When 56 G 30 B 14 The domain wall in the electrode starts to propagate along the current direction at a speed of 0.5 μm / s. The domain wall motion is measured in four configurations with two configurations of domain walls and two current directions, eliminating the influence of the ambient magnetic field.

[0049] Figure 8 Different configurations of domain walls of ferrimagnetic materials pinned by weak domain walls as described in Example 1 (30.2%) and ) Schematic diagram of domain wall motion under low current density (the duration of the pulse current is 2 seconds, the starting position of the domain wall is indicated by a green line, and the scale bar is 50 μm). Figure 8 It can be seen that in Co 56 G 30 B 14 The current density required to stimulate domain wall motion (1.8 kA / cm 2 The current density required to excite a skyrmion with a similar velocity is more than an order of magnitude lower (e.g., 35 kA / cm in Co-Fe-B). 2 When it is about 15 μm / s, please refer to Jiang, W. et al. Science 349, 283-286 (2015).).

[0050] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A ferrimagnetic material with weak domain wall pinning, characterized in that: In terms of atomic percentage, it includes 0-100% of transition elements, 0-100% of rare earth elements and 0-100% of doping elements, the sum of the transition elements, rare earth elements and doping elements is 100%, and the atomic percentage of the transition elements in the ferrimagnetic material pinned by the weak domain wall is greater than the atomic percentage of the rare earth elements and the doping elements, and the atomic percentage of the rare earth elements and the doping elements in the ferrimagnetic material pinned by the weak domain wall is not 0; The doping elements include boron and / or nitrogen.

2. The ferrimagnetic material with weak domain wall pinning according to claim 1, characterized in that: The ferrimagnetic material is an amorphous structure.

3. The ferrimagnetic material with weak domain wall pinning according to claim 1, characterized in that: The transition elements include one or more of Fe, Co and Ni.

4. The ferrimagnetic material with weak domain wall pinning according to claim 1, characterized in that: The rare earth elements include one or more of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc and Y.

5. The ferrimagnetic material with weak domain wall pinning according to any one of claims 1 to 4, characterized in that: The transition element is Co, the rare earth element is Gd, and the doping element is B.

6. The ferrimagnetic material with weak domain wall pinning according to claim 5, characterized in that: The atomic percentage of Co in the ferrimagnetic material pinned by the weak domain wall is 10.0% to 80.0%, the atomic percentage of Gd in the ferrimagnetic material pinned by the weak domain wall is 10.0% to 80.0%, and the atomic percentage of B in the ferrimagnetic material pinned by the weak domain wall is 10.0% to 80.0%.

7. The weak domain wall pinned ferrimagnetic material according to claim 6, characterized in that: The atomic ratio of Co to B is 9:1 to 3:

1.

8. Use of the weak domain wall pinned ferrimagnetic material according to any one of claims 1 to 7 in magnetic storage spin electronics devices, magnetic logic spin electronics devices, magnetic field sensors or new soft magnetic materials.

Citation Information

Patent Citations

  • Rare earth sintered magnet and method for production thereof

    CN101031984A

  • Method for rapidly preparing nano biphasic composite permanent-magnetic material through carrying out heating by utilizing electron beam

    CN106205919A

  • Activation function generator based on magnetic domain wall driving type magnetic tunnel junction and preparation method

    CN113193110A

  • Memory and electronic equipment

    CN116711477A

  • Method for obtaining chiral coupling in ferrous magnetic alloy

    CN117737668A